Regional Convergence in Germany. A Geographically Weighted Regression Approach - Hans-Friedrich Eckey; Reinhold Kosfeld; Matthias Turck (European Regional Science Association (ERSA), 2006)
Regional convergence of German labour markets represents a politically important question. Different studies have examined convergence processes in Germany. We derive equations to estimate the speed of convergence on the basis of an extended Solow model. The technique of geographically weighted regression permits a detailed analysis of convergence processes, which has not been conducted for Germany so far yet. It allows to estimate a separate speed of convergence for every region resulting from the local coefficients of the regression equations. The application of this technique to German labour market regions shows regions moving with a different speeds towards their steady states. The half-live times in the model of conditional convergence disperse less than the same coefficients in the absolute convergence model. Moreover, the speed of convergence is substantially slower in the manufacturing sector than in the service sector.
Keywords: 330